2016
DOI: 10.1002/bab.1495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extremely low‐frequency electromagnetic fields on antioxidant activity in the human keratinocyte cell line NCTC 2544

Abstract: Some epidemiological studies have suggested possible associations between exposure to extremely low-frequency electromagnetic fields (ELF-EMFs) and various diseases. Recently, ELF-EMF has been considered as a therapeutic agent. To support ELF-EMF use in regenerative medicine, in particular in the treatment of skin injuries, we investigated whether significant cell damage occurs after ELF-EMF exposure. Reactive oxygen species (ROS) production was evaluated in the human keratinocyte exposed for 1 H to 50 Hz ELF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 59 publications
3
22
1
3
Order By: Relevance
“…Different cell lines used in researches is another factor that affects the results and conclusions. Even environment conditions like extremely low‐frequency electromagnetic fields are possible to impact on the antioxidant activity of cells . Compared with newly artificially synthesized antioxidants, natural or endogenous antioxidants might be less risky having unexpected impacts on patients or animals.…”
Section: Perspectivesmentioning
confidence: 99%
“…Different cell lines used in researches is another factor that affects the results and conclusions. Even environment conditions like extremely low‐frequency electromagnetic fields are possible to impact on the antioxidant activity of cells . Compared with newly artificially synthesized antioxidants, natural or endogenous antioxidants might be less risky having unexpected impacts on patients or animals.…”
Section: Perspectivesmentioning
confidence: 99%
“…Previous studies have demonstrated that ELF-EMF is associated with production of ROS. [16][17][18] Moreover, reduced PDYN expression in the human brain is associated with opiate dependency. 35,36 Interestingly, in the present study the continuous exposure condition of ELF-EMF was associated with the lower expression levels of the PDYN.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been reported that ELF-EMF enhanced production of reactive oxygen species (ROS). [16][17][18] Cells maintain redox balance through production of ROS and cellular antioxidant capacity. The altered balance between generation and elimination of ROS plays a critical role in a variety of multifactorial complex traits including neurodegenerative diseases.…”
mentioning
confidence: 99%
“…et al, Demers et al, 2014). Headache, decreased learning potential, poor concentration, and oxidative stress were reported (Calcabrini et al, 2017 andAhmed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%